2015
DOI: 10.1021/jp513019z
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Al-Doped ZnO Nanoclusters for CO Chemical Sensors

Abstract: Experimental work has already demonstrated that Al-doped ZnO nanostructures exhibit a higher response than the pure ZnO sample to CO gas and can detect it at sub-ppm concentrations. In this work, using density functional theory calculations (at B3LYP, M06-L, and B97D levels), we studied the effect of Al-doping on the sensing properties of a ZnO nanocluster. We investigated several doping and adsorption possibilities. This study explains the electrical behavior that has been obtained from the ZnO nanostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
148
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 397 publications
(160 citation statements)
references
References 42 publications
12
148
0
Order By: Relevance
“…C is a material constant. It has been shown that [38] equation 2 is compatible with the experimental results, and the electrical conductivity increases by decreasing the E g , and vice versa. It should be noted that this equation works only for semiconductors in which by increasing the temperature the electrical conductivity will be increased.…”
Section: Si-doped Bnntsupporting
confidence: 68%
See 2 more Smart Citations
“…C is a material constant. It has been shown that [38] equation 2 is compatible with the experimental results, and the electrical conductivity increases by decreasing the E g , and vice versa. It should be noted that this equation works only for semiconductors in which by increasing the temperature the electrical conductivity will be increased.…”
Section: Si-doped Bnntsupporting
confidence: 68%
“…As can be seen in Fig. 4, the E g value of the Si N -BNNT is obviously decreased from 2.48 to 1.91 eV (by about 23.0% change) in the adsorbed form, which would result in an electrical conductivity change of the defected sheet according to the following equation [38]:…”
Section: Si-doped Bnntmentioning
confidence: 97%
See 1 more Smart Citation
“…In theoretical studies, the electrical conductance has been commonly simulated by the HOMO-LUMO gap (E g ) change of semiconductor sensor based on the following equation [57]: σ = AT 3/2 exp(−E g /2kT ) (4) where k is the Boltzmann's constant and A (electrons/m 3 K 3/2 ) is a constant. It has been shown that the results of this equation are in good agreement with the experiment [57]. Herein, we will discuss the sensitivity of borophene toward HCOH using this equation.…”
Section: Electronic Properties and Sensing Behaviormentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 4 engineering such as chemical functionalization, doping impurity atoms, decoration by transition metals, generating defects, etc [36][37][38][39][40][41].…”
Section: A N U S C R I P Tmentioning
confidence: 99%